FRI0033 Trends in the incidence of orthopaedic surgeryin patients with rheumatoid arthritis in spain. a national observational cohort study. (12th June 2018) - Mazzucchelli, R.; Quirós, J.; Peña, M.; Perez-Fernandez, E.; Crespí, N.; Macía Villa, C.; Espinosa, M.; Villaverde, V.; Morell Hita, J.L.; Martinez-Prada, C.; García-Vadillo, A.; Morado Quiroga, C.; et al.
Abstract : Background: The need of orthopaedic surgery (OS) is a marker of disease severity in RA. During the last 20 years, the treatment in RA has changed, incorporating strategies based on "treat-to-target" and biological therapies. But, have these new strategies modified the incidence of OS in RA? Objectives: To analyse the incidence and trend of hospital admissions for OS in patients with RA, in Spain, during the period between 1999 and 2015. Methods: This is a national retrospective population based study. We analysed a national administrative database that includes a Minimum Basic Data Set (MBDS) of all hospital admissions of patients with RA. Period: 1999 to 2015. The OS were identified by the presence of ICD9 codes for arthrodesis, Total Hip Arthroplasty -THA-, Total Knee Arthroplasty -TKA-, Total Superior Limb Arthroplasty -TSLA. The population at risk was estimated through the population census of the National Institute of Statistics. The adjusted rates of hip fracture were calculated, by sex and age. The trend was analysed by Generalised Linear Models (GLM). Results: Of a total of 338.343 hospital admissions, 21.088 (6, 62%) were for OS. The main clinical-demographic characteristics are shown in the next table 1. The mean age of OS increased 6 years during the study period (p<0, 001). The OS age-adjusted rate during the study period was 752, 9/10 5 inhab-year. The global fracture age-adjusted remained stable during de study period (IRR 1, 002; IC95% 0, 9–1, 01). In RA patients>60 the rate increase while in RA <60 years the rate decrease (figure 1). Conclusions: In Spain, during the period from 1999 to 2015, the global incidence rate of orthopaedic surgery in patients with RA has remained stable. In RA patients>60 years the rate increase while in RA <60 years the rate decrease. The mean age of OS increased 6 years. Disclosure of Interest: None declared